2017
DOI: 10.1126/sciadv.1603024
|View full text |Cite
|
Sign up to set email alerts
|

A nearly water-saturated mantle transition zone inferred from mineral viscosity

Abstract: The mantle transition zone contains 1 to 2 weight % water based on the viscosity difference between ringwoodite and bridgmanite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
71
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(79 citation statements)
references
References 44 publications
6
71
2
Order By: Relevance
“…Although a number of studies have suggested a water‐rich MTZ, from investigations of observed ringwoodite diamond inclusions (Pearson et al, ) to regional seismological analyses of reflected phases (e.g., Schmandt et al, ), electrical conductivity models (e.g., Karato, ), and laboratory measurements of mineral viscosity (Fei et al, ), our study suggests a regional variability in possible water content even beneath subduction zones that is more complex than previously thought.…”
Section: The Origin Of Radial Anisotropy In the Mtz: Water Content Immentioning
confidence: 44%
“…Although a number of studies have suggested a water‐rich MTZ, from investigations of observed ringwoodite diamond inclusions (Pearson et al, ) to regional seismological analyses of reflected phases (e.g., Schmandt et al, ), electrical conductivity models (e.g., Karato, ), and laboratory measurements of mineral viscosity (Fei et al, ), our study suggests a regional variability in possible water content even beneath subduction zones that is more complex than previously thought.…”
Section: The Origin Of Radial Anisotropy In the Mtz: Water Content Immentioning
confidence: 44%
“…Regional-scale seismic studies suggest variable water content of the MTZ (Courtier & Revenaugh, 2006;Emry et al, 2015;Liu et al, 2016;Van der Lee et al, 2008;Van der Meijde et al, 2003); however, recent viscosity measurements of hydrated ringwoodite suggest a globally saturated transition zone (Fei et al, 2017). Evaluating the regional-scale water content of the MTZ is important to understanding Earth's deep water cycle (Hirschmann, 2006;Jacobsen & Van der Lee, 2006;Karato, 2011;Ohtani et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Based on an observation of a low SH velocity layer and high V p / V s , Li et al () suggested a hydrated MTZ in this region according to the experiment by Jacobsen and Smyth (), who pointed out the velocity discordance between the compressional and shear wave on hydrous ringwoodite. The presence of water in the MTZ has also been revealed by petrological and other geophysical studies and predicted by mineral physics experiments (e.g., Fei et al, ; Houser, ; Mao et al, ; Pearson et al, ; Wang et al, ). If we attribute the ~2.7% increase of V p / V s ratio to the water effect alone, then the water content would be ~1.2–1.8 wt% in the MTZ beneath Northeast Asia based on the experimental data on iron‐bearing wet ringwoodite (Jacobsen et al, ; Jacobsen & Smyth, ; Thio et al, ).…”
Section: Discussionmentioning
confidence: 73%
“…Some researchers suggested that the MTZ beneath Northeast Asia is hydrous (0.2-0.4 wt %; Li et al, 2013;Ye et al, 2011) due to intensive hydration by ancient slab subduction and stagnation (Kuritani et al, 2011) through water transport into deep mantle (Ohtani et al, 2004;Song et al, 2007). More recently, Fei et al (2017) argued that the MTZ should be nearly water-saturated (1-2 wt %) globally based on mantle viscosity fitting result. On the other hand, some researches believed that little water exists in the MTZ (e.g., Houser, 2016;Yoshino et al, 2008).…”
Section: Introductionmentioning
confidence: 99%